Implementation of Hadith on the Influence of Parenting Style on Child Development : Implementasi Hadis tentang Pengaruh Gaya Parenting Orang Tua terhadap Perkembangan Anak - Nurul Inayah, Nadia; Agung Danarta; Muhammad Alif (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2024)
The parent's role in the legal action of building children's character is to encounter new situations along with modern times. Various new challenges are undeniable, such as social, cultural, and economic issues, and the increasingly massive development of digital technology. It should affect the parenting process, where parents are required to observe and control everything that their children do. This study was conducted to find out the hadith commentary on the concept of